Humility in Learning from Al-Kahf 66 for Solution Students’ Moral Crisis in the Digital Era - Yusron Nur Hadi; Nurul Laely Mahmudah; Hayati Tohsatu; Lutfiyah Lutfiyah (IQRO: Journal of Islamic Education, 2026)
The digital era has brought extraordinary ease in accessing information and knowledge. However, this convenience has also given rise to new moral challenges among students, such as intellectual arrogance, declining learning ethics, and reduced respect for teachers. This study aims to examine Qur’an Surah Al Kahf verse 66 through the approach of Ulum-al Qur’an, analyze the value of humility in seeking knowledge based on classical and contemporary tafsir, and formulate its relevance as a solution to students’ moral crisis in the digital era. This study employs a qualitative approach using a library research method by analyzing various classical and contemporary tafsir literature, particularly Tafsir Ibn Kathir and Tafsir Al Misbah. The findings show that the dialogue between Prophet Musa and Prophet Khidir in Qur’an Al Kahf verse 66 illustrates the importance of humility in the learning process, where even a person of high knowledge demonstrates humility to acquire understanding. This value of humility can be implemented to reduce arrogant behavior, strengthen respect toward teachers, and cultivate sincerity in learning. Thus, humility becomes an ethical and spiritual foundation relevant for building students’ character in the digital era.